Manajemen Pelayanan Administrasi Kependudukan Tutul WhatsApp di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Magetan - Priyanto Susiloadi; Gina Putri Kartika (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
This study aims to determine how the Management of Population Administration Services by WhatsApp (PAKTUWA) in the Department of Population and Civil Registration of Magetan Regency and to find out there is or not a gap that occurs in the service management. This study uses the service triangle model describing a service triangle model based on strategy, frontline people or HR, and friendly customer system. Gap model described to find out there is or not a gaps between gap 1 - 5 in the service management. This is a descriptive qualitative research, through interviews, observations and documentation studies. The sample selected by purposive sampling, The data validity used source triangulation. Data analysis technique uses Miles and Huberman model. The results of this study, the management of population administration services using whatsapp (PAKTUWA) in the population and civil registration office Magetan district at system indicators, human resources run smoothly, but the actual indicators have been running well but not optimal because the technology in SIAK only has one server and often experiences down so as to result in service to the community is hampered. While in customer indicators there are people who feel that the procedure of this program is too complicated for people who do not often use a phone. Gap that occurs is in Gap 1 lack of lean service structure, gap 2 there is a lack of reward to employees and Gap 3 is a technology problem that down hampers employee work and service to the community.